Maximal kidney length predicts need for native nephrectomy in ADPKD patients undergoing renal transplantation - Cristea, Octav (Canadian Medical Association, 2014)
INTRODUCTION: Native nephrectomy in patients with autosomal dominant polycystic kidney disease (ADPKD) is performed on a case-by-case basis. We determine if pre-transplant maximal kidney length (MKL) can be used to predict ultimate nephrectomy status. METHODS: We performed a retrospective review of ADPKD patients who underwent renal transplantation at our centre between January 2000 and December 2012. Pre-transplant measurements of MKL alone, MKL adjusted for height (HtMKL), weight (WtMKL) and body mass index (BMI-MKL) were each assessed for their predictive ability via a receiver operating characteristic (ROC) curve analysis. RESULTS: In total, 84 patients met our inclusion criteria, of which 17 (20.2%) underwent native nephrectomy. An MKL ROC curve analysis revealed an area under the curve (AUC) of 0.867 (95% confidence interval [CI] 0.775–0.931; p < 0.001). An optimal cutoff criterion of >21.5 cm revealed a sensitivity of 94.1% (95% CI 71.3–99.9) and specificity of 70.1% (95% CI 57.7–80.7) for eventual nephrectomy. The AUC of HtMKL, WtMKL and BMI-MKL ROC curves did not differ significantly from MKL alone. HtMKL improved specificity, but not overall test performance. The determination of the cut-off MKL may be influenced by the single-centre retrospective nature of this analysis, as well as the fact that renal size was determined by ultrasound and not computerized tomography or magnetic resonance imaging. CONCLUSION: MKL in patients with ADPKD is associated with the eventual need for nephrectomy and may be a useful clinical tool to risk stratify these patients and therefore guide patient conversations to a decision to leave the native kidneys in situ.